(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Deep Brain stimulation is well accepted now as amethod for treating refractory parkinsons disease. Objective:To describe deep brain stimulation in Iraq, emphasize the technically demanding procedure and to discuss the results on the patients after six years of follow up. Methods: A clinical prospective study of 8 patients with Parkinson’s disease underwent deep brain stimulation surgery in the Neurosciences Hospital. We performed 18 multiple stages operations from October 2007 to June 2008. The procedure begins with proper selection of patients, pre operative radiological studies, planning for targeting the subthalamic nucleus, the operation stage and the programming stage, which usually starts one-week post operatively. Results:One patient developed subarachnoid hemorrhage, another one have miss targeting and required retargeting surgery. A part from these complications all the patients had satisfactory outcome in controlling their symptoms during the six years follow up period. Conclusion:Deep brain stimulation is indicated for the treatment of refractory Parkinson disease. However it needs a well skilled personnel working as a team. The future of deep brain stimulation is remarkable as the list of indications is continually increasing to include other disease modalities. Key words:Parkinson’s disease, deep brain stimulation, functional neurosurgery.